Increasing Motivation And Cognitive Learning Outcomes Of Grade 4 Elementary School Students In Science Subjects, Material On Changes In Form Of Objects Through The Project Based Learning (PjBL) Learning - Ronalia Ronalia (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The aim of this research is to improve learning outcomes in science subjects by applying the PjBL learning model to students in class 4A of SD Muhammadiyah 1 Ketelan Surakarta and to increase motivation to learn science subjects by applying the PjBL learning model to students in class 4A of SD Muhammadiyah 1 Ketelan Surakarta. This type of research is classroom action research using a qualitative and quantitative approach. This class Action Research consists of 2 cycles, each cycle consists of 4 stages, namely: (1.) Planning; (2.) Implementation of Action; (3.) Observation and Evaluation; (4.) Reflection. The results of classroom action research showed an increase in student motivation, which was initially 57%, increasing by 5% to 62%. As well as increasing student cognitive learning outcomes, in cycle II the number of students who got a score > 80 increased to 25 students or as much as 96% and students who got a score < 80 decreased from the initial 4 students to 2 students or as much as 4%. it was concluded that the learning outcomes usedProject Based Learning can increasing motivation and learning outcomes for grade IV science at SD Muhammadiyah 1 Ketelan Surakarta for the 2023/2024 academic year.